Pengaruh Kepemimpinan Terhadap Kinerja Karyawan Pada Gerai Burger Indonesia Cabang Panam Pekanbaru - yapentra, arhipen (Sekolah Tinggi Ilmu Ekonomi Riau, 2025)
This study investigates how leadership influences employee performance at the Burger Indonesia outlet in Panam Pekanbaru, Riau. A census of 38 employees was surveyed using Likert‑scaled questionnaires, and simple linear regression was applied. Results reveal that leadership has a positive and significant effect on performance (β = 0.564, t = 4.093, p < 0.001), explaining 31.8 percent of performance variance (R² = 0.318). Employees perceive leadership practices—especially motivation, participative decision‑making, and clear delegation—as key drivers of higher work quality, timeliness, and productivity. Nevertheless, disciplinary data and absenteeism records indicate areas where leadership enforcement could improve. The study recommends that managers intensify participatory decision‑making, consistent sanctions, and regular motivation sessions to sustain performance. Future research should integrate additional variables (e.g., work environment, compensation) to capture the remaining 68.2 percent of unexplained variance